Exploiting impedance shaping approaches to overcome force overshoots in delicate interaction tasks. (29th September 2016) - Roveda, Loris; Pedrocchi, Nicola; Tosatti, Lorenzo Molinari
The aim of the presented article is to overcome the force overshoot issue in impedance based force tracking applications. Nowadays, light-weight manipulators are involved in high-accurate force control applications (such as polishing tasks), where the force overshoot issue is critical (i.e. damaging the component causing a production waste), exploiting the impedance control. Two main force tracking impedance control approaches are described in literature: (a) set-point deformation and (b) variable stiffness approaches. However, no contributions are directly related to the force overshoot issue. The presented article extends both such methodologies to analytically achieve the force overshoots avoidance in interaction tasks based on the on-line estimation of the interacting environment stiffness (available through an EKF). Both the proposed control algorithms allow to achieve a linear closed-loop dynamics for the coupled robot-environment system. Therefore, control gains can be analytically on-line calculated to achieve an over-damped closed-loop dynamics of the controlled coupled system. Control strategies have been validated in experiments, involving a KUKA LWR 4+. A probing task has been performed, representative of many industrial tasks (e.g. assembly tasks), in which a main force task direction is defined.